Histological findings of tracheal samples from COVID‐19 positive critically ill mechanically ventilated patients. (18th October 2021) - Ward, Patrick Alexander; Collier, Jonathan Marc; Weir, Justin; Osborn, Michael; Hanley, Brian; Smellie, William James Buchanan; ,
Abstract: Objectives: This study examines the histological findings of tracheal tissue samples obtained from COVID‐19 positive mechanically ventilated patients, to assess the degree of tracheal inflammation/ulceration present. Design and participants: Retrospective single‐centre observational cohort study. All patients admitted to Adult Intensive Care Unit (AICU) with COVID‐19 infection, requiring mechanical ventilation and surgical tracheostomy between 1 April and 1 May 2020, were included ( Group 1 ). Tracheal windows excised at tracheostomy underwent histological analysis. Comparison was made with: tracheal windows from COVID‐19 positive AICU ventilated patients admitted between 1 January and 1 March 2021 ( Group 2 ); tracheal windows from COVID‐19 negative AICU ventilated patients ( Group 3 ); and, tracheal autopsy samples from COVID‐19 positive patients that died without undergoing prolonged mechanical ventilation ( Group 4 ). Results: G roup 1 demonstrated mild/moderate inflammation (tracheitis) in nearly all samples (15/16, 93.8%), with infrequent micro‐ulceration (2/16, 12.5%). G roup 2 demonstrated similar mild/moderate inflammation in all samples (17/17, 100%), with no ulceration. Histological findings of Groups 1 and 2 COVID‐19 positive patients were similar to Group 3 COVID‐19 negative patients, which demonstrated mild/moderate inflammation (5/5, 100%), with uncommon superficial erosion (1/5, 20%). Group 4 demonstrated mild chronic inflammation or no significant inflammation, with uncommon micro‐ulceration (1/4, 25%). Conclusions: Severe tracheal inflammation was not demonstrated in mechanically ventilated COVID‐19 positive patients at the level of the second/third tracheal rings, at the stage of disease patients underwent tracheostomy. Histological findings were similar between mechanically ventilated COVID‐19 positive and negative patients. Tracheal ulceration may be a feature of early or severe COVID‐19 disease.